Analysis Factors Influencing Financial Management Behavior - Purwanto, Setiyo; Fathihani Fathihani; Yanthy Herawaty Purnama (Dinasti International Journal of Economics, Finance & Accounting, 2023)
Financial management is a person's behavior in managing finances as managing planning, budgeting, checking, managing, controlling, searching, and saving finance funds that arise because of someone's habits and a sense of responsibility for finances. The low level of understanding of financial management for millennials tends to be consumptive, giving rise to various irresponsible financial behaviors. The purpose of this research is to find out that final knowledge, final attitude, and self-efficacy can affect financial management behavior. The result of this research expects to contribute to the millennial generation being wiser in managing finances and prioritizing needs over wants. The population used is the Millennial General in the Jakarta region. The sample used was 100 respondents spread across the Jakarta area. Data collection operated using a questionnaire method in which respondents answered questions arranged in the form of choices and scaled using a Likert scale (1-5). The system used in this study is a quantitative analysis using SEM analysis tools and SmartPLS 3.3 tools.